亞洲教育品質之觀察 - 王如哲(Ru-Jer Wang) (Journal of Education Research (Print), 2019)
The purpose of this article is to observe education quality in Asia by the use of documentary analysis. Main documents employed in this study are made by international organizations such as the World Bank, OECD, IEA, etc. The content of this article includes five sections. The first section is to illustrate the intangible and tangible factors behind education quality in Asia. The second is concerned with definition of education quality. The third one is then to look at education quality in Asia based on the evidence of three aspects as years and expenditure of compulsory education, and educational achievements of international comparison. This is followed by the fourth section of higher education quality in Asia which comprises university ranking, internationalization ranking of higher education institutions. Challenges for education in Asia are concluded in the fi nal part of this paper